High prevalence of vitamin D insufficiency in professional handball athletes - Bauer, P.; Henni, S.; Dörr, O.; Bauer, T.; Hamm, C. W.; Most, A. (The Physician and Sportsmedicine, 2019)
Objectives: Vitamin D affects multiple body functions through the regulation of gene expression. In sports medicine, its influence on musculoskeletal health and performance is of particular interest. Vitamin D insufficiency might decrease athletic performance and increase the risk of musculoskeletal injuries. Several studies have demonstrated vitamin D deficiency in professional athletes; however, the prevalence of vitamin D insufficiency in professional handball players is yet unknown.